An Injectable Platform of Engineered Cartilage Gel and Gelatin Methacrylate to Promote Cartilage Regeneration - Xu, Wei; Wang, Tao; Wang, Yahui; Wu, Xiaodi; Chen, Yujie; Song, Daiying; Ci, Zheng; Cao, Yilin; Hua, Yujie; Zhou, Guangdong; Liu, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Cell–hydrogel constructs are frequently used as injectable platforms for irregular cartilage regeneration. However, cell–hydrogel constructs have obvious disadvantages, such as long culture times, high probability of infection, and poor cartilage formation capacity, significantly limiting their clinical translation. In this study, we aimed to develop a novel injectable platform comprising engineered cartilage gel (ECG) and gelatin methacrylate (GelMA) to improve cartilage regeneration. We first prepared an ECG by cutting the in vitro engineered cartilage sheet into pieces. The chondrocytes and ECG were evenly encapsulated into GelMA to form Cell-GelMA and ECG-GelMA constructs. The ECG-GelMA construct exhibited preferred gel characteristics and superior biocompatibility compared with the Cell-GelMA construct counterpart. After subcutaneous implantation in nude mice and goat, both gross views and histological evaluations showed that the ECG-GelMA construct achieved more homogenous, stable, and mature cartilage regeneration than the Cell-GelMA construct. Immunological evaluations showed that ECG-GelMA had a mitigatory immunologic reaction than the Cell-GelMA construct. Overall, the results suggest that the ECG-GelMA is a promising injectable platform for cartilage regeneration that may advance clinical translation.